2005
DOI: 10.1146/annurev.publhealth.24.100901.140910
|View full text |Cite
|
Sign up to set email alerts
|

WATER AND BIOTERRORISM: Preparing for the Potential Threat to U.S. Water Supplies and Public Health

Abstract: Key Words water terrorism, waterborne disease, intentional water contamination, biowarfare agents, biotoxins ■ Abstract Water supplies and water distribution systems represent potential targets for terrorist activity in the United States because of the critical need for water in every sector of our industrialized society. Even short-term disruption of water service can significantly impact a community, and intentional contamination of a municipal water system as part of a terrorist attack could lead to serious… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
40
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(40 citation statements)
references
References 38 publications
0
40
0
Order By: Relevance
“…Viability tests are important in the detection of C. parvum oocysts in environmental samples, since only viable oocysts pose a threat to public health (37). The massive devastating consequence of the waterborne cryptosporidiosis outbreak in Milwaukee, WI, in 1993 also illustrates the potential destructive effect of C. parvum during accidental or intentional contamination scenarios (39,46). Our previous study showed that surface soil can serve as a major source of C. parvum introduced to the environment by cattle ranching (30).…”
mentioning
confidence: 96%
“…Viability tests are important in the detection of C. parvum oocysts in environmental samples, since only viable oocysts pose a threat to public health (37). The massive devastating consequence of the waterborne cryptosporidiosis outbreak in Milwaukee, WI, in 1993 also illustrates the potential destructive effect of C. parvum during accidental or intentional contamination scenarios (39,46). Our previous study showed that surface soil can serve as a major source of C. parvum introduced to the environment by cattle ranching (30).…”
mentioning
confidence: 96%
“…Questions have been asked regarding the possibility of our drinking water becoming contaminated with biothreat agents and the efficacy of current disinfection practices for the reduction in viability (inactivation) of biothreat agents (5,8,14). The use of UV irradiation as a supplemental water disinfection practice is increasing for several reasons, among them improving control of protozoa, such as Cryptosporidium spp., and decreasing disinfection by-products created by chemical disinfectants (21 anthracis was grown on soil extract-peptone-beef extract agar (SEA) (1) or in Schaeffer's sporulation medium (SSM) (10) for 7 days, resulting in Ͼ99% spores as determined by phase-contrast microscopy.…”
mentioning
confidence: 99%
“…The primary identification of the water born pathogen appeared to be from the health services, prior to water contamination monitoring from regulatory sources. The May 2015 Prague contamination incident is perhaps a reflection of reality, that prior to any deliberate contamination being recognised by scientific or technological assessment, people may be deceased or ill, with the primary alert issued from medical services (Meinhardt, 2005). Prague 6, the identified region of this contamination is the area where most foreign missions and embassies are located in Prague.…”
Section: Contamination Of Water Supply and Responsementioning
confidence: 99%
“…Although there is no universal blueprint or exact model for terrorist attack planning strategies there are commonalities and strategies from other successful attacks that the various groups have learnt from, with the cross fertilization evident in personnel exchanges, training and information sharing between various cells and groups (Drake, 1998). Indeed as numerous studies indicate, water is a soft target and some attack planning has occurred internationally over the past 10 years (Kalil and Berns, 2004, Kroll et al, 2010a, Kroll, 2012b, Meinhardt, 2005, Meinhardt, 2006 related to water services.…”
Section: Figure 4: Typical Components Of Terrorist Attack Planningmentioning
confidence: 99%